Designing markets for biodiversity offsets: Lessons from tradable pollution permits. Issue 6 (18th March 2019) - Needham, Katherine; de Vries, Frans P.; Armsworth, Paul R.; Hanley, Nick
Abstract: Globally, governments and regulators face an ongoing trade‐off between meeting economic development needs and conserving biodiversity. Markets for biodiversity offsets are one tool which could secure biodiversity protection at lower costs to society whilst allowing some economic development to still take place. We provide a new perspective on biodiversity offset markets by focussing on what can be learnt from one of the best‐researched environmental markets: the market for tradable pollution permits. We argue there are four key design parameters in terms of how and what to trade. These design parameters likely determine the ecological effectiveness and economic efficiency of any market in biodiversity offsets. Policy Implications . Applying lessons from tradable pollution permit markets will be important if the benefits of biodiversity offset markets are to be realized more fully in future. A well‐functioning market for biodiversity offsets dually minimizes the economic costs of preventing future losses in biodiversity due to development and provides an economic incentive for landowners to invest in biodiversity conservation. The most crucial aspect of the market is what to trade (the currency in the offset market), and this has significant implications on the other key aspects of market design; the trading ratio which governs the rate of exchange between offsets at different points in space and time; the scale of the market; and how the market is regulated. We argue that markets function best where the conservation priority is a well‐defined unit of biodiversity which can be readily measured and monitored. In situations where there are already strong regulations safeguarding biodiversity, the benefit of biodiversity offset markets is in reducing the aggregate costs of conservation. We believe biodiversity offset markets will offer the highest potential in developing countries with weaker environmental protection and a greater need to reconcile economic development needs with conservation under limited funding.